Analisis Ergonomi Lingkungan Pabrik Tahu Berdasarkan Parameter Fisik Kerja - Triansyah, M. Agus; Cahyono, Cahyono; Siregar, Mulki; Wiwin, Wiwin (Universitas Muhammadiyah Sorong, 2025)
This study aims to evaluate the working environment based on physical parameters, including lighting, noise, temperature, and humidity, at RR tofu factory in Cikampek, Karawang. A quantitative approach was used through field observations and direct measurements at 11 designated work points. The measurement results were compared against the standards set by the Indonesian Ministry of Manpower Regulation No. 5 of 2018 and relevant international guidelines. Findings show that the average lighting intensity was 148 lux, which falls below the minimum standard of 200 lux, and the Uniformity Ratio of 0.061 indicates poor light distribution. The average noise level was 77 dBA, below the threshold of 85 dBA for 8-hour workdays, with a noise dose of 15.75%, indicating a safe condition. However, the Temperature Humidity Index (THI) values in all areas indicate a